Characterization for index based livestock insurance - Mills, C.J.; Jensen, Nathaniel D.; Barrett, Christopher B.; Mude, Andrew G. (International Livestock Research Institute, 2016)
Pastoral populations of sub-Saharan Africa are particularly vulnerable to losses in wealth and productive assets via herdmortality shocks. Although conventional insurance mechanisms covering individual losses are not cost effective in low income extensive grazing pastoral communities, index insurance for livestock offers a promising alternative. This paper identifies regions most suitable for an index-based livestock insurance product: areas predicted to have high covariaterisk from drought, high potential demand for a livestock insurance product, and supporting market infrastructure for an insurance product. Our findings support current efforts to implement index insurance in Kenya and Ethiopia, and reveal additional areas for geographic expansion in western and southern Africa.